GOUT ARTHRITIS - Eva Roswati (LPPM Universitas Abdurrab, 2024)
A 47-year-old male patient came to the emergency room with complaints of joint pain for 2 days and worsened in the last 1 day. Complaints are felt in all joints, especially in the joints of the hands, knees and feet, the pain appears suddenly at night, and continuously, the pain feels like stabbing. Before the patient experienced this complaint, the patient had eaten meat rendang and coconut milk vegetable katu toge and ate vein meatballs. At the time of the complaint, the patient felt stiffness in the joints making it difficult to walk. The patient also felt that his hands, knees and feet had swollen since the complaints of pain appeared. The patient admits that this is not the first time he has experienced complaints like this. In addition to pain in the joints, the patient also complained of tightness since 1 day, tightness worsens if lying on his back and decreases if the patient is sitting, fever for 2 days with a temperature of 38 0C, chills at night, difficulty sleeping and the whole body feels pain, decreased appetite since the complaint, defecation and urination within normal limits. The patient had experienced a similar thing Â± 3 years ago. patients routinely take herbal medicine. The patient works as a self-employed, the patient is an active smoker. On physical examination, it was found that the patient's general condition appeared moderately ill, the patient's nutritional status was level 1 obesity with a BMI of 26.5 kg/m2. The patient was in a febrile condition with a body temperature of 37.9 0C, there was an increase in respiratory rate of 22x / m, oxygen saturation of 95% with free air. Examination of cor and pulmo and abdomen within normal limits. On examination of the extremities, there were signs of rubor, dolor, and caloric inflammation in both hand joints, knee joints and foot joints. There was also tofus on digiti 1 pedis dextra. Therapy was given a low purine renal diet, and medication.